RETRACTED: Leukocyte telomere length and obesity in children and adolescents: A systematic review and meta-analysis - Farhangi, Mahdieh A.; Lame, Amir-Hossein (Frontiers in Genetics, 2022)
Background: Several studies revealed the negative effects of adiposity on telomere length shortening. However, the results of studies that assessed the negative relationship between obesity and leukocyte telomere length (LTL) are not consistent. Here, we decide to perform a systematic review and meta-analysis to pool the results of articles that assessed this association among children and adolescents. Methods: The online databases such as PubMed, Embase, Proquest and Scopus were searched until June 2021. Cross-sectional studies that evaluated the relationship between obesity and LTL among apparently healthy children and adolescents (age ≤ 18 years) were eligible for this study. Studies that had reported mean ± standard deviation of LTL, were considered. The random-effects model was used to assess the pooled weighted mean difference (WMD) and 95% CI. Results: The search yielded seven studies from an initial 3,403 records identified. According to summarization of the results of seven articles with 4,546 participants, obesity was associated with LTL shortening among children and adolescents (WMD = -0.082; CI: -0.135, -0.020; P = 0.002; I2 = 99.9%). No publication bias was observed. According to the results of subgrouping, the significant results were only attributed to the studies that were recruited in Europe, had high quality score, studies among overweight and obese adolescents, with baseline LTL lower than 1Kbp and were performed in community-based school settings. None of these variables could explain the high between-study heterogeneity. Conclusion: We observed shorter LTL among obese/overweight adolescents and children in a systematic review and meta-analysis. Further longitudinal prospective studies with large sample size are required to obtain more reliable results.